Withaferin A Regulates LRRK2 Levels by Interfering with the Hsp90- Cdc37 Chaperone Complex - Narayan, Malathi; Zhang, Juan; Braswell, Kaitlyn; Gibson, Chelsea; Zitnyar, Ashley; C. Lee, Daniel; Varghese-Gupta, Sheeba; K. Jinwal, Umesh (Current Aging Science, 2015)
Leucine-Rich Repeat Kinase 2 (LRRK2) is a large, multi-domain protein that has been found to be mutated in patients with familial and sporadic Parkinson’s disease, Alzheimer’s disease and Crohn’s disease. While the functions of LRRK2 are still largely unclear and mutations in LRRK2 are associated with adverse gain-of-function activities such as increased kinase activity, increased levels of LRRK2 alone are associated with toxicity in neurons. Consequently, exploring mechanisms to decrease levels of LRRK2 using pharmacological inhibitors would be highly advantageous. Previous work has shown that the chaperone heat shock protein 90 (Hsp90) and its co-chaperone Cdc37 interact with and stabilize LRRK2. In the current study, we explore the regulation of LRRK2 by withaferin A (WA), a potent inhibitor of the interaction between Hsp90 and Cdc37. We report that treatment of the microglial cell line N9 with WA causes a decrease in cellular levels of LRRK2 in a dose- and time-dependent manner. We also find that treatment with WA disrupts the interaction between Hsp90, its co-chaperone Cdc37 and LRRK2, which leads to the destabilization and decreased levels of LRRK2. Additionally, treatment with celastrol, which is also an inhibitor of the Hsp90-Cdc37 complex, decreased LRRK2 levels. Interestingly, treatment with WA in the presence of celastrol enhanced the clearance of LRRK2. Overall, our data suggest that LRRK2 levels can be regulated by targeting the Hsp90-Cdc37 complex, which may have implications in the search for therapeutic strategies for Alzheimer’s disease, Parkinson’s disease and other LRRK2 proteinopathies.
Keywords: LRRK2